The Relationship Between Family Support and Quality Of Life in Adolescents With Thalassaemia Major - Angela Merici Wenefrida Kurniawati; Rika Monika (Sahabat Publikasi Kuu, 2025)
Background: Indonesia is the third largest country in the world in terms of Thalassaemia cases, this number is projected to increase by 2.500 new cases each year. Thalassaemia is chronic disease that can affect quality of life. Providing family support is one effort to improve the quality of life of sufferers. Purpose: To determine the relationship between family support and the quality of life in adolescents with Thalassaemia Major at POPTI Solo Raya. Methods: This cross-sectional study involved 72 adolescents with Thalassaemia Major aged 11-19 years using Purposive Sampling at POPTI Solo Raya. Data was collected using validated instruments: family support questionnaire and Assesment of Qualityiof Life-4 Dimension (AQoL-4D) and analyzed using the Spearman Rank test. Results: the age of repondents mayority aged between 11 – 14 years old, with 81,9% reporting had good family support dan 95,8% reporting had a good quality of life. The result showed family support was positively associated with quality of lfe (r = 0,295, p = 0.012). Conclusions: Thalassaemia can affect the quality of life of adolescent patients. By increasing family support during the patient's treatment, it will positively impact the patient's quality of life.